2017
DOI: 10.1007/s10067-017-3822-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren’s syndrome: Extraglandular manifestations and hydroxychloroquine therapy

Abstract: The use of hydroxychloroquine (HCQ) in Primary Sjögren's Syndrome (pSS) has been assessed in different studies over the last years, with conflicting results regarding its efficacy in sicca syndrome and extraglandular manifestations (EGM). The goal of this study was to compare the incidence rate of EGM in pSS patients with and without HCQ therapy.We performed a multicenter retrospective study, including patients with pSS (European classification criteria) with at least 1 year of follow-up. Subjects with concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…8 There are currently no approved diseasemodifying treatments for pSS. Small, open-label, uncontrolled and controlled clinical efficacy studies of methotrexate, 9 leflunomide, 10 hydroxychloroquine, 11 rituximab, [12][13][14] epratuzumab (B-celltargeted agents), 15 belimumab (B-cell-activating factor-blocking agent) 16 What does this study add? ► Abatacept treatment did not result in significant clinical efficacy versus placebo in this randomised controlled trial, but it showed evidence of disease-relevant biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…8 There are currently no approved diseasemodifying treatments for pSS. Small, open-label, uncontrolled and controlled clinical efficacy studies of methotrexate, 9 leflunomide, 10 hydroxychloroquine, 11 rituximab, [12][13][14] epratuzumab (B-celltargeted agents), 15 belimumab (B-cell-activating factor-blocking agent) 16 What does this study add? ► Abatacept treatment did not result in significant clinical efficacy versus placebo in this randomised controlled trial, but it showed evidence of disease-relevant biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…292 EGMs were less frequent in those treated with HCQ (36.5 vs. 63.5%, p < 0.01). 292 Furthermore, the following manifestations were more common in the untreated group: arthritis (p < 0.001); fatigue (p < 0.01); purpura p ¼ 0.01); RP (p ¼ 0.003); and hypergammaglobulinemia (p ¼ 0.006). Immunosuppressive agents were used in 28 (12.7%), 13 of who were receiving HCQ.…”
Section: Corticosteroids and Immunosuppressive Agentsmentioning
confidence: 88%
“…Optimal treatment of SS is controversial, as a paucity of RCTs has been done. 289 Corticosteroids (CS), immunosuppressive agents (IA), 290 disease modifying antirheumatic drugs (DMARD), 2,290 and hydroxychloroquine (HCQ) [291][292][293] are often used 294 (►Table 3), but appropriate indications have not been ascertained. Unequivocal responses to systemic CS or IA have been noted in some patients with SS and extraglandular involvement.…”
Section: Corticosteroids and Immunosuppressive Agentsmentioning
confidence: 99%
See 2 more Smart Citations